ASPEK EKSPERIENTAL KONSUMEN DAN PENERAPANNYA BAGI PEMASAR - Andhi Johan S (Pro Bisnis, 2009)
The tight competition structure (there are so many products that have the same benefit), the channel of communication change (to be a channel of entertain-ment), the improvement ability of information technology (IT), and the existence of brand personality (formely brand image) make the costumer needs unable be fulfilled with standart strategy. Its motivate marketer create a new strategy through understanding of emotional customer side. Marketer try to satisfy customer from the side of feeling, emotional, and all sense through experiences that make them happy, surprise, fantasites, and fun. It’s called experiental marketing.